Model Desain Sistem Informasi Parking Services Management PT Mitra Usaha Jaya Utama - Budiman Muhamad; Magnaz Lestira Oktaroza (Bandung Conference Series: Accountancy, 2022)
Abstract. Parking services are services for providing off-street parking spaces or for parking vehicles in parking areas, whether provided as a form of business. This business of providing parking services must be followed by the use of a good information system. PT. Mitra Usaha Jaya Utama is a company that provides parking services. From the results of the research conducted, it was found that the problems that arise from the operational activities of the demand for parking services and the management of parking services, therefore this study aims to analyze, design and provide improved solutions for the information system that is being implemented. The research method used by the designer in providing system improvement solutions is descriptive analysis research methods and case studies through the System Development stages using the FAST system development (Frame work for the application of system technique) and using the JAD (Join application Development) development technique stages. by conducting interviews, observations and documentation of all activities related to the operations of PT. Jaya Utama Business Partner. The result of this design is to create a management information system that is interconnected and the resulting data is the latest and accurate data and is easily understood by its users. Abstrak. Jasa parkir adalah jasa penyediaan tempat parkir diluar badan jalan atau pelayanan memarkirkan kendaraan di area parkir, baik yang disediakan sebagai bentuk usaha. Usaha penyediaan jasa parkir ini harus diikuti dengan penggunaan sistem informasi yang baik. PT. Mitra Usaha Jaya Utama adalah salah satu perusahaan yang menyediakan jasa parkir. Dari hasil penelitian yang dilakukan ditemukan permasalahan - permasalahan yang timbul dari aktivitas operasional permintaan jasa parkir dan pengelolaan jasa parkir, maka dari itu penelitian ini bertujuan untuk menganalisis, mendesain dan memberikan solusi perbaikan dari sistem informasi yang sedang diterapkan. Metode penelitian yang digunakan oleh perancang dalam memberikan solusi perbaikan sistem yaitu metode penelitian deskriptif analisis dan studi kasus melalui tahapan System Development yang menggunakan pengembangan system FAST (Frame work for the application of system technique) dan dengan menggunakan tahapan teknik pengembangan JAD (Join application Development) dengan melakukan wawancara, observasi dan dokumentasi segala aktivitas yang berhubungan kegiatan operasi PT. Mitra Usaha Jaya Utama. Hasil dari perancangan ini adalah menciptakan sistem informasi pengelolaan yang saling terhubung dan data yang dihasilkan merupakan data yang terbaru dan akurat serta mudah dimengerti oleh penggunanya.